2022
DOI: 10.1016/j.celrep.2021.110222
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine import and accumulation causes immunomodulation in macrophages engulfing apoptotic cells

Abstract: Highlights d Efferocytosis triggers macrophages to accumulate polyamines spermidine and spermine d Polyamine accumulation is mediated by Rac1-dependent endocytic import d Inhibition of polyamine import blunts immunomodulation in response to efferocytosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Ornithine may result from apoptotic cell-derived arginine metabolized by arginase-1 ( 73 ). An increased arginase-1 activity in mouse efferocytic macrophages has been confirmed in another study ( 84 ). Then, ornithine may be transformed via ornithine decarboxylase (ODC) into putrescine.…”
Section: Efferocytosis As a Critical Step Triggering The Resolution P...supporting
confidence: 54%
See 2 more Smart Citations
“…Ornithine may result from apoptotic cell-derived arginine metabolized by arginase-1 ( 73 ). An increased arginase-1 activity in mouse efferocytic macrophages has been confirmed in another study ( 84 ). Then, ornithine may be transformed via ornithine decarboxylase (ODC) into putrescine.…”
Section: Efferocytosis As a Critical Step Triggering The Resolution P...supporting
confidence: 54%
“…Amino-acid levels increase after efferocytosis as a consequence of apoptotic cell-derived protein/peptide degradation. This concerns, in particular arginine, ornithine, lysine and methionine, while no increase of alanine and glycine is detected ( 73 , 84 ). Ornithine may result from apoptotic cell-derived arginine metabolized by arginase-1 ( 73 ).…”
Section: Efferocytosis As a Critical Step Triggering The Resolution P...mentioning
confidence: 98%
See 1 more Smart Citation
“…We used spermidine, among the other polyamines, as it has been proved to suppress tumorigenesis in healthy tissues and, in tumors, it contributed to the modulation of cancerrelated functions, including immunoregulation, autophagy, and apoptosis [31]. In the tumor microenvironment, in particular, spermidine can induce the autophagy-dependent release of ATP, which, in turn, promotes immune surveillance [32,33]. Additionally, spermidine demonstrated the ability to alter macrophage immunometabolism and stimulate CD8+ T-cells [34] and memory B-cell responses [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tumor cell apoptosis and subsequent efferocytosis by neighboring and/or infiltrating immune cells may enhance the immunosuppressive phenotype. McCubbrey et al demonstrated that LPS-stimulated macrophages co-cultured with apoptotic Jurkat cells exhibited increased spermine uptake and reduced IL1β and IL6 gene expression, while treatment with the Rac-1 inhibitor NSC23766 abolished the increase in polyamine content and reverted IL1β and IL6 expression to near-normal levels [7]. Thus, investigating immune-cell-intrinsic alterations upon systemic DFMO treatment alone and/or in combination with transport inhibitors may provide insight into the anti-tumor efficacy or lack thereof in these treatment groups.…”
Section: Immune Cell-intrinsic Deficiencies In Polyamine Biosynthesis...mentioning
confidence: 99%